The Development of Performance-based Model Authentic Assessment on Archival Subject - Pratiwi, D; Arief, M; Churiyah, M (KnE Social Sciences, 2018)
The developed assessment models use two types of test or non-test instruments which are divided into three aspects: performance, knowledge, and social behavior [23]. The purpose of this research is to develop a product in the form of an authentic assessment instrument package based on the performance of Archival Subject in Vocational High School using the research and development research technique. Borg and Gall describe the expedient of the instruments through expert validations & readability try-outs and describing the result of the implementation using the quasiexperimental method design by using the technique of analyzing the quantitative and qualitative data. Authentic assessment model is developed as an assessment model that constructs learning [36] and increases the concept of knowledge, behavior, and skills of the students comprehensively and objectively to fulfill the assessment criteria. Keywords: authentic assessment, performance assessment, archival learning, vocational high school